2003
DOI: 10.1016/s0168-6496(02)00428-2
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of mixtures of aromatic and chloroaliphatic hydrocarbons by aromatic hydrocarbon-degrading bacteria

Abstract: The well-characterized toluene-oxidizing bacteria Pseudomonas putida PaW1, P. putida F1, P. mendocina KR1, Burkholderia cepacia G4, B. cepacia JS150, and Ralstonia pickettii PKO1, as well as several strains of bacteria isolated from activated sludge, were examined for their ability to degrade mixtures of aromatic and chloroaliphatic hydrocarbons. Collectively, the strains tested were able to transform all of the 14 aromatic hydrocarbons included in the mixtures, with most strains degrading five or more. Few st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Xylene is metabolized to mono-methylated catechol. Therefore, it is quite obvious that bacteria in a combination would be able to utilize BTX compounds more effectively and efficiently than degradation by an individual isolate of the same consortium, which may be by virtue of the production of different degradative enzymes by mixed microbial population (Leahy et al 2003). …”
Section: Analysis Of Aliphatic and Aromatic Fractions By Gas Chromatomentioning
confidence: 99%
“…Xylene is metabolized to mono-methylated catechol. Therefore, it is quite obvious that bacteria in a combination would be able to utilize BTX compounds more effectively and efficiently than degradation by an individual isolate of the same consortium, which may be by virtue of the production of different degradative enzymes by mixed microbial population (Leahy et al 2003). …”
Section: Analysis Of Aliphatic and Aromatic Fractions By Gas Chromatomentioning
confidence: 99%
“…Commonly identified isolates appear to fall within two phyla, the Proteobacteria (c and b Proteobacteria) and Actinobacteria. Proteobacteria (c or b) include, for example, microorganisms within the genera Pseudomonas (Alagappan and Cowan 2003; Bertoni et al 1996;Irie et al et al 2003;Reardon et al 2002), Burkholderia (Alagappan and Cowan 2003;Johnson and Olsen 1997;Leahy et al 2003;Radway et al 1998;Reardon et al 2002), Ralstonia (Alagappan and Cowan 2003;Leahy et al 2003;Olsen et al 1994), Achromobacter (Yeom et al 1998;Yeom and Yoo 1999), Pseudoxanthomonas (Kim et al 2008), Hydrogenophaga (Fahy et al 2008b), Alicycliphilus (Weelink et al 2008) and Acinetobacter (Kim and Jeon 2009). Benzene degraders belonging to the phylum Actinobacteria include microorganisms in the genera Rhodococcus (Deeb and Alvarez-Cohen 1999;Fahy et al 2008b;Jung and Park 2004;Na et al 2005) and Arthrobacter (Fahy et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we referred to the HM-1 isolate as Ralstonia sp. The activities of Ralstonia picketti such as poly (3-hydroxybutyrate)-degradation (Takanashi and Saito, 2006), removal of phenanthrene (Chávez-Gómez et al, 2003), and aromatic hydrocarbon-degradation (Leahy et al, 2003) have been reported.…”
mentioning
confidence: 99%